PRIORITY AREAS OF INNOVATION IN CORPORATE STRATEGIES OF MULTINATIONAL PHARMACEUTICAL COMPANIES IN GLOBAL COORDINATES - Yaroslava Stoliarchuk; Nataliya Moskalyuk; Roman Simonov (Izdevnieciba "Baltija Publishing", 2023)
The purpose of the article is to substantiate global trends in the research and innovation activities of multinational pharmaceutical companies and to identify key directions of transformation in corporate innovation strategies in the context of increased international competition in the global pharmaceutical market. Methodology. The methodological basis of the work is the following methods of scientific research: dialectical, historical-logical, system-structural analysis of economic processes and phenomena, analysis and synthesis, the method of quantitative and qualitative comparisons. Results. One of the key global sustainable development goals of the United Nations for the period up to 2030 is to ensure the health and well-being of nations, which in global terms can be achieved primarily on the basis of the large-scale research activities of multinational pharmaceutical companies and the systematic commercialisation of the results of corporate research and development. In recent decades, under the influence of technoglobalisation processes, the innovatisation of pharmaceutical companies' activities has accelerated. It finds its concentrated expression in the steady increase of R&D costs, diversification of their structure, mass commercialisation of innovative developments and strengthening of their transdisciplinarity, accelerated capitalisation of R&D costs, etc. According to the world experience, the most effective innovative strategies of pharmaceutical companies today are such as mergers and acquisitions, strategic alliances of pharmaceutical and biotechnology companies, innovative outsourcing and insourcing, cointegration and pseudo-concentration, corporatisation of patent portfolios and research technologies, venture financing of R&D of pharmaceutical companies. At the same time, mergers and acquisitions are increasing the capitalisation of the global pharmaceutical industry, strengthening its expansion into global markets, redistributing its regional segments and diversifying the sources of funding for pharmaceutical companies' research activities. Value/оriginality. Current trends and features of corporate strategy formation in multinational pharmaceutical companies are identified. Strategic orientations of research activities of pharmaceutical companies in specialised areas of clinical research in the context of therapeutic categories are determined. The process of capitalisation of pharmaceutical companies is analysed and the tendency to activate the use of corporate mergers and acquisitions (M&A) strategy in the pharmaceutical business is revealed. It is proposed to create strategic alliances of multifunctional pharmaceutical companies with biotech companies using the M&A strategy. It is recommended that pharmaceutical companies strengthen their innovation orientation in the design of their strategies by combining patent portfolios and research technologies, as well as jointly implementing large-scale innovation programmes and projects.